Worm-control practices, anthelmintic use and its implication on anthelmintic resistance in gastrointestinal nematodes of sheep in Rajasthan - SWARNKAR, C P; SINGH, D (The Indian Journal of Animal Sciences, 2010)
The base line information on management of sheep flocks with greater emphasis on worm control practices was collected from sheep farmers of Rajasthan. The status of anthelmintic resistance in gastrointestinal nematodes against commonly available anthelmintics (benzimidazole, tetramisole and closantel) was determined through faecal egg count reduction test, and results were correlated with flock-management practices. Information obtained from this study indicates lack of knowledge about worm-control strategies, anthelmintic use and the problem of anthelmintic resistance among the majority of sheep farms. There is high prevalence of benzimidazole resistance (86.4%) and moderate prevalence of tetramisole resistance (55.7%) with distinct regional variation. The existing drench frequency is not justifiable and there is a high opportunity to harvest the benefits of agro-climatic conditions, grazing resources and practices to save money by avoiding unnecessary en-mass treatments in sheep flocks of Rajasthan. The predominance of Haemonchus contortus (Rudolphe, 1803) and use of all types of anthelmintics revealed that there is a need to educate farmers and extension workers on appropriate anthelmintics to be used in their locality. Animals shared the same pasture sources particularly in monsoon and post-monsoon season, thus to prevent borrowing and probability of emergence of multiple resistance. There is a need to coordinate farmers in all management systems at a community or village level with respect to use of anthelmintic type for a particular year with greater involvement of researchers, pharmaceuticals, field veterinarian and extension workers.